Discussion-Based Online Teaching to Enhance Student Learning: Theory, Practice and Assessment – Tisha Bender - Simmons, Laura K. (Teaching theology and religion, 2006)
Books reviewed: Discussion-Based Online Teaching to Enhance Student Learning: Theory, Practice and Assessment. By Tisha Bender. Sterling, Virginia: Stylus Publishing, 2003. xviii + 206 pages. ISBN 1-57922-065-7. USD24.95 (paperback).